Menopausal Hormone Therapy and Long-Term All-Cause and Cause-Specific Mortality: The Women's Health Initiative Randomized Trials. Issue 1 (January 2018) - Manson, JoAnn E.; Aragaki, Aaron K.; Rossouw, Jacques E.; Anderson, Garnet L.; Prentice, Ross L.; LaCroix, Andrea Z.; Chlebowski, Rowan T.; Howard, Barbara V.; Thomson, Cynthia A.; Margolis, Karen L.; Lewis, Cora E.; Stefanick, Marcia L.; et al.
Abstract : (Abstracted from JAMA 2017;318(10):927–938) This study was a further investigation of the data accumulated in the hormone trials of the Women's Health Initiative (WHI). While the general results derived from the WHI hormone trials have been reported previously, this study focused on the long-term follow-up of the all-cause mortality rates.